Spiritual Intelligence Moderates the Relationship Between Psychological Well-Being, Role Stress and Auditor Performance - Nursabilla, Thahira Qarimma; Gayatri, Gayatri; Suprasto, Herkulanus Bambang; Sari, Maria Mediatrix Ratna (E-Jurnal Akuntansi; Vol 31 No 6 (2021)DO - 10.24843/EJA.2021.v31.i06.p06, 2021)
The purpose of this study is to investigate the impact of psychological well-being and role stress on auditor performance, with spiritual intelligence serving as a moderating variable. The data collection for this study was obtained from a questionnaire and was collected at the Bali Province Public Accountant Office. The sample was determined using a purposive sampling method with 54 auditors from the Bali Province Public Accountants as respondents. In this study, the interaction test MRA was used to analyze data. According to the findings of the study, psychological well-being has a positive effect on auditor performance. This research also shows that role stress can impair auditor performance. Auditors' spiritual intelligence has the potential to strengthen the relationship between psychological well-being and auditor performance. On the other hand, spiritual intelligence mitigates the impact of role stress on auditor performance. Keywords: Psychological Well-Being; Stress; Auditor Performance; Spiritual Intelligence.